Surgical Management of Large Occipital Encephalocoele: A Case Report - SK, Sim; SC, Theophilus; AR, Noor Azman (IIUM Medical Journal Malaysia, 2014)
Cranium dysraphism occur less commonly than spinal dysraphism. Overall, occipital encephalocoeles are more frequent than anterior encephalocoes. A large occipital encephalocoele possess difficulty in surgical intervention, not only the sac contains large amount of herniated brain tissue, but the appropriate positioning for successful intubation as well as the higher rate of surgical complications such as cerebrospinal fluid leakage and skin necrosis. In this case report, surgical management of large occipital encephalocoele is discussed. The use of antibiotics in ruptured encephalocoele is recommended.